Survival and behavior of the telescope snail Telescopium telescopium (LINNE) at different salinities. - Prosia, Easter Joy Pamati-an
The influence of salinity on the survival and behavior of common fishpond pest Telescopium telescopium was determined in order to use as basis for controlling the snail's population in the ponds. The circadian rhythm of the snail was also included to serve as additional information on the snail's behavior. The snails were exposed for 18 days in each test salinities, 0, 10, 20, 30, 40, and 50 ppt with three replicates for every treatments. Survival and behavior observations were done every three days. Another set of snails was observed and whose locomotor rhythm was monitored every three hours over a 24 hour period., T. telescopium was found to tolerate and exhibit normal activity at salinities 10 - 50 ppt. In freshwater, it retracted into its shell throughout the experiment and can only survive at most 15 days. The snail's circadian rhythm has a fundamental period of 24 hours and is affected by day-night cycles. They were more active at or towards midnight and least active during daytime. It was suggested that regular flooding in of freshwater is beneficial to eliminate or at least reduce the population of T. telescopium in the ponds